A multi-outcome analysis of the effects of treatment timing in the management of zygomatic fractures. Issue 1 (January 2016) - Hurrell, M.J.L.; Borgna, S.C.; David, M.C.; Batstone, M.D.
Abstract: The aim of this study was to analyze the effects of surgical treatment delay in the management of zygomatic fractures. A retrospective case series of 99 patients was undertaken. Four outcome measures were analyzed in relation to delay: facial symmetry, facial scarring, trismus, and radiographic outcome. Five additional variables were subsequently analyzed: operation, diagnosis, primary operator, regular alcohol use, and regular cigarette use. Statistically significant associations were found between delay and facial scarring, and delay and radiographic outcome. For each additional delay of a day, the odds of facial scarring being present, compared to absent, decreased by 13% (odds ratio (OR) 0.87, 95% confidence interval (CI) 0.76–0.98). For regular cigarette users, for each additional day of delay there was a 306-fold increased risk of having a radiographic outcome of major deviation from premorbid compared to equivalent to premorbid (OR 306.38, 95% CI 2.08–45, 161.49). For non-regular cigarette users/non-users, for each additional day of delay there was a 1.5-fold increased risk of having a radiographic outcome of major deviation from premorbid compared to equivalent to premorbid (OR 1.50, 95% CI 1.08–2.09). These findings correlate with commonly held beliefs and anecdotal evidence. Despite the limitations, this study allows for an evidence-based approach to the timing of treatment of zygomatic fractures.